2009
DOI: 10.1111/j.1467-9280.2009.02359.x
|View full text |Cite
|
Sign up to set email alerts
|

Action Understanding in the Superior Temporal Sulcus Region

Abstract: The posterior superior temporal sulcus (STS) region plays an important role in the perception of social acts, although its full role has not been completely clarified. This functional magnetic resonance imaging experiment examined activity in the STS region as participants viewed actions that were congruent or incongruent with intentions established by a previous emotional context. Participants viewed an actress express either a positive or a negative emotion toward one of two objects and then subsequently pic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
90
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 156 publications
(100 citation statements)
references
References 32 publications
(37 reference statements)
10
90
0
Order By: Relevance
“…Second, topographic maps have shown that this activation is focused on central (sensorimotor) areas rather than lateral, temporal sites (e.g., Marshall and Meltzoff, 2011;Paulus et al, 2012a). Although we therefore suggest that our temporal activation asymmetry is not related to mu-desychronization and action mirroring in the motor system, the relation between the right temporal areas and people's ability to understand others' actions (Reid et al, 2005;van der Cruyssen et al, 2009;Vander Wyk et al, 2009) may suggest a role of action understanding in competent instrumental helping.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Second, topographic maps have shown that this activation is focused on central (sensorimotor) areas rather than lateral, temporal sites (e.g., Marshall and Meltzoff, 2011;Paulus et al, 2012a). Although we therefore suggest that our temporal activation asymmetry is not related to mu-desychronization and action mirroring in the motor system, the relation between the right temporal areas and people's ability to understand others' actions (Reid et al, 2005;van der Cruyssen et al, 2009;Vander Wyk et al, 2009) may suggest a role of action understanding in competent instrumental helping.…”
Section: Discussionmentioning
confidence: 86%
“…Recent findings suggested a relation between the right temporal areas and people's ability to understand others' actions (van der Cruyssen et al, 2009;Vander Wyk et al, 2009; see also Reid et al, 2005). Our results could therefore suggest that infants' growing ability for action understanding plays a dominant role in the development of instrumental helping behavior.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In that study, which used a functional MRI (fMRI) paradigm with typically developing subjects, a strong effect of context was observed in the right posterior STS region: observation of gaze shifting away from a target (incongruent shifts) evoked a haemodynamic response with extended duration and greater amplitude compared to gaze shifting towards the target (congruent shifts). In a similar study from the same group, also performed in typically developing subjects, STS presented a greater response when participants viewed a reaching gesture incongruent with a prior emotional expression than when they viewed a reaching gesture congruent with the prior expression, regardless of whether expectations were induced by a positive or a negative emotional expression [45]. Consistent with prior studies in adults, the STS, middle temporal gyrus, and inferior parietal lobule were sensitive to the intentions underlying the stimulus character's eye movements.…”
Section: Social Perception and Social Cognition: Implication Of The Tmentioning
confidence: 95%
“…In addition, studies have demonstrated that STS responds not only to biological movement itself but also to specific aspects of social gestures, including "the intentionality and appropriateness of biological motion" [4,44,45]. Indeed, STS activation has been reported in response to possible versus impossible human movements [46] and meaningful versus non-meaningful hand motions [47], as well as to the intentionality of other observed human actions including reaching-to-grasp movements of the arm and hand [48].…”
Section: Social Perception and Social Cognition: Implication Of The Tmentioning
confidence: 99%